KEBIJAKAN LUAR NEGERI INDONESIA DALAM MENANGANI KASUS PERDAGANGAN MANUSIA DI KAWASAN ASIA TENGGARA - maulid dina, siti rahmah (Journal Ilmu Sosial, Politik dan Pemerintahan, 2023)
Human trafficking is a global issue that is growing so rapidly, especially in Southeast Asia. this happens because of the encouragement of economic factors such as poverty and social factors such as education. The government has a very big responsibility in preventing human trafficking, especially in its territory as stated in the Universal Declaration of Human Rights. Therefore, it is necessary to review Indonesia's foreign policy in dealing with cases of human trafficking in the Southeast Asian region. This study uses a descriptive method and an explanatory approach, this study also uses the concepts of foreign policy and Human Security. The results of this study are in an effort to eradicate cases of human trafficking, there are often obstacles due to the lack of strict laws and regulations governing human trafficking at the national level. Indonesia has implemented Law number 21 of 2007, discussing the criminal act of trafficking in persons (UU PTPPO), and establishing an integrated service for empowering women and children (P2TPP2A). In addition, Indonesia also makes foreign policies related to cases of human trafficking, such as cooperation with other countries.